Cooperation Between the USSR and Nicaragua in the Conditions of the Sandinista Revolution - A. V. Baranov (Ибероамериканские тетради)
The article defines the preconditions and main directions of cooperation between the USSR and Nicaragua in the conditions of the Sandinista revolution in 1979–1990. The topic of the article is relevant for studies of Soviet foreign policy in Latin America in economic, military, ideological and socio-cultural aspects, and it also allows to identify the prerequisites for the return to cooperation between the Russian Federation and Nicaragua in the post-Soviet period of history. The article applies the paradigm of neorealism in international studies, which makes it possible to determine the resources of influence, interests and institutional framework of the USSR’s foreign policy towards Nicaragua, to compare the declared and real tasks of foreign policy. Comparative-historical and structural-functional methods are used.The course of the Soviet foreign policy towards revolutionary Nicaragua had both geopolitical and ideological motivations. Nicaragua was a promising springboard for the establishment of revolutionary regimes in other countries of Central America. The country also occupied a key position for the construction of an inter-oceanic canal, an alternative to the Panama Canal. In Soviet literature of the 1980s the Sandinista revolution was seen as national-liberation, anti-imperialist, but not socialist. Soviet experts positively assessed the strategic alliance of the Sandinista National Liberation Front (FSLN) with the supporters of the revolution among the believers. Sandinism was regarded as an effective, albeit controversial, revolutionary ideology. The periodization of the Soviet foreign policy towards Nicaragua during 1979–1990 is substantiated: the establishment of cooperation relations (1979–1981), the highest point in cooperation (1982–1987), the curtailment of cooperation as the national reconciliation policy (1987–early 1990) was unfolding. The main factor in the dynamics of bilateral relations were the strategic interests of the USSR in Central America, which changed dramatically under the influence of perestroika. The defeat of the FSLN in the 1990 elections was largely the result of the Soviet foreign policy deideologization and the collapse of socialism in the Eastern European countries.